Active energy ray-curable adhesive sheet and display device
By using a diene-based copolymer with (meth)acrylate site in the adhesive sheet of the display device, combined with (meth)acrylic polymer and a photopolymerization initiator, post-curing of the adhesive sheet in the prior art is solved by combining the adhesive sheet with a (meth)acrylic polymer and a photopolymerization initiator. Due to insufficient rear adhesive force, a display device adhesive sheet with high initial adhesive force and impact resistance is achieved.
Patent Information
- Application Number
- CN202210448497.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-04-28
- Filing Date
- 2022-04-26
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2042-04-26
AI Technical Summary
In the prior art, the active energy ray-curing adhesive sheet used in the display device has insufficient adhesion after post-curing and has low initial adhesion, making it difficult to meet the needs of high performance and precision.
By using a diene-based copolymer having a (meth)acrylate site at both ends as a component of the binder composition, combined with a (meth)acrylic polymer and a photopolymerization initiator, an active energy with excellent performance was prepared by combining a (meth)acrylic polymer and a photopolymerization initiator. Radiation curing adhesive sheet.
The high initial adhesion and post-curing adhesion of the active energy ray-cured adhesive sheet are achieved, which reduces water vapor transmission and improves impact resistance. It is suitable for high performance and precision displays. Device.
Smart Images

Figure BDA0003616364260000291 
Figure BDA0003616364260000301
Abstract
Description
Technical Field
[0001] The present invention relates to an active energy ray-curable pressure-sensitive adhesive sheet and a display device. Background Art
[0002] Adhesive sheets are used, for example, to bond components to each other, and are widely used in various fields. In recent years, such adhesive sheets have also been used for display devices such as liquid crystal displays (LCDs), or input devices such as touch panels. By using adhesive sheets to bond components such as optical displays constituting display devices or input devices to each other, various devices can be manufactured with high precision and ease.
[0003] As an example of an adhesive sheet, an active energy ray-curable adhesive sheet is known (for example, see Patent Document 1). Such an active energy ray-curable adhesive sheet has the property of being cured by irradiating active energy rays (that is, by post-curing). Therefore, when the active energy ray-curable adhesive sheet is irradiated with active energy rays in a state where adherends are bonded to each other, the active energy ray-curable adhesive sheet is cured, so that the adherends are bonded to each other more firmly.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: International Publication No. 2017 / 022770 Summary of the invention
[0007] Problem that the invention aims to solve
[0008] However, in recent years, in the field of display devices and the like, the performance of adhesive sheets used for bonding displays has been further improved and precision has been further promoted. Therefore, there is also a strong demand for improving the performance of adhesive sheets used for bonding displays, etc. From this point of view, it is imperative to develop an active energy ray-curable adhesive sheet that has excellent performance as an adhesive sheet after post-curing.
[0009] The present invention has been made in view of the above, and an object of the present invention is to provide an active energy ray-curable pressure-sensitive adhesive sheet having excellent performance as a pressure-sensitive adhesive sheet and a display device using the pressure-sensitive adhesive sheet.
[0010] Solutions for solving problems
[0011] The present inventors have conducted intensive studies to achieve the above object and have found that the above object can be achieved by using a diene copolymer having (meth)acrylate moieties at both ends, thereby completing the present invention.
[0012] That is, the present invention includes, for example, the subject matters described in the following items.
[0013] Item 1
[0014] An active energy ray-curable adhesive sheet comprising: a semi-cured product of an adhesive composition comprising at least a (meth)acrylic polymer, a photopolymerization initiator, and a diene copolymer having (meth)acrylate moieties at both ends;
[0015] When the adhesive force to glass before curing with active energy rays is X1 and the adhesive force to glass after curing with active energy rays is X2, X1 is 20 N / 25 mm or more and the value of X1 / X2 is 0.8 or more.
[0016] Item 2
[0017] An active energy ray-curable adhesive sheet comprising: a semi-cured product of an adhesive composition comprising at least a (meth)acrylic polymer, a photopolymerization initiator, and a diene copolymer having (meth)acrylate moieties at both ends;
[0018] When the water vapor permeability before curing with active energy rays is defined as Y1 and the water vapor permeability after curing with active energy rays is defined as Y2, Y1 is 200 g / (m 2 24hr) or less,
[0019] The value of Y1 / Y2 is less than 1.5.
[0020] Item 3
[0021] An active energy ray-curable adhesive sheet comprising: a semi-cured product of an adhesive composition comprising at least a (meth)acrylic polymer, a photopolymerization initiator, and a diene copolymer having (meth)acrylate moieties at both ends;
[0022] When the gel fraction of the semi-cured material is defined as Z1 and the gel fraction of the semi-cured material after post-curing under active energy rays is defined as Z2, the value of (Z1 / Z2)×100 is 71 or more and 95 or less.
[0023] Item 4
[0024] The active energy ray-curable pressure-sensitive adhesive sheet according to any one of items 1 to 3, wherein the pressure-sensitive adhesive composition contains less than 5 parts by mass of the monofunctional acrylic monomer having a molecular weight of less than 1000 per 100 parts by mass of the (meth)acrylic polymer.
[0025] Item 5
[0026] The active energy ray-curable adhesive sheet according to any one of items 1 to 3, wherein in the adhesive composition, the content of the monofunctional acrylic monomer is less than 5 parts by mass per 100 parts by mass of the (meth)acrylic polymer, and the monofunctional acrylic monomer has an alkyl group with a carbon number of 8 to 24, and the alkyl group has a linear or branched structure.
[0027] Item 6
[0028] The active energy ray-curable pressure-sensitive adhesive sheet according to any one of items 1 to 3, wherein the diene copolymer is a polymer having a 1,2 vinyl structure or a polymer having a structure in which a 1,2 vinyl structure is hydrogenated.
[0029] Item 7
[0030] The active energy ray-curable pressure-sensitive adhesive sheet according to any one of items 1 to 3, wherein
[0031] The weight average molecular weight of the diene copolymer is 1000 to 5000.
[0032] The glass transition temperature of the diene copolymer is 0° C. or lower.
[0033] Item 8
[0034] The active energy ray-curable pressure-sensitive adhesive sheet according to any one of items 1 to 3, wherein the pressure-sensitive adhesive composition contains 0.5 to 30 parts by mass of the diene copolymer based on 100 parts by mass of the (meth)acrylic polymer.
[0035] Item 9
[0036] The active energy ray-curable pressure-sensitive adhesive sheet according to any one of items 1 to 3, wherein the relative dielectric constant at 100 kHz after active energy ray curing is 3.5 or less.
[0037] Item 10
[0038] The active energy ray-curable pressure-sensitive adhesive sheet according to any one of items 1 to 3, which is used for laminating members for liquid crystal or organic EL displays.
[0039] The aforementioned component is glass, a polarizing plate, or a touch sensor.
[0040] Item 11
[0041] A display device comprising a post-cured product of the active energy ray-curable adhesive sheet according to any one of items 1 to 3 as an adhesive layer.
[0042] Effects of the Invention
[0043] The present invention can provide an active energy ray-curable pressure-sensitive adhesive sheet having excellent performance as a pressure-sensitive adhesive sheet and a display device using the pressure-sensitive adhesive sheet. DETAILED DESCRIPTION
[0044] Hereinafter, the embodiments of the present invention will be described in detail. It should be noted that in this specification, the expressions "contain" and "include" include the concepts of "contain", "include", "consist essentially of", and "consist only of".
[0045] 1. Active energy ray curable adhesive sheet
[0046] The active energy ray-curable pressure-sensitive adhesive sheet of the present invention includes an active energy ray-curable pressure-sensitive adhesive sheet A, an active energy ray-curable pressure-sensitive adhesive sheet B, and an active energy ray-curable pressure-sensitive adhesive sheet C.
[0047] The active energy ray-curable pressure-sensitive adhesive sheet A comprises:
[0048] A semi-cured product of an adhesive composition comprising at least a (meth) acrylic polymer, a photopolymerization initiator, and a diene copolymer having a (meth) acrylate moiety at both ends. For the active energy ray-curable adhesive sheet of the present invention, when the adhesive force to the glass before curing with active energy rays is set to X1 and the adhesive force to the glass after curing with active energy rays is set to X2, X1 is 20N / 25mm or more, and the value of X1 / X2 is 0.8 or more. The active energy ray-curable adhesive sheet A of the present invention has excellent initial adhesive force.
[0049] The active energy ray-curable pressure-sensitive adhesive sheet B comprises:
[0050] A semi-cured product of an adhesive composition comprising at least a (meth)acrylic polymer, a photopolymerization initiator, and a diene copolymer having (meth)acrylate moieties at both ends. For the active energy ray-curable adhesive sheet of the present invention, when the water vapor permeability before curing with active energy rays is defined as Y1 and the water vapor permeability after curing with active energy rays is defined as Y2, Y1 is 200 g / (m 2 · 24 hr) or less, and the value of Y1 / Y2 is less than 1.5. The active energy ray-curable pressure-sensitive adhesive sheet B of the present invention has a low water vapor transmission rate.
[0051] The active energy ray-curable pressure-sensitive adhesive sheet C includes:
[0052] A semi-cured product of an adhesive composition comprising at least a (meth)acrylic polymer, a photopolymerization initiator, and a diene copolymer having (meth)acrylate moieties at both ends. For the active energy ray-curable adhesive sheet of the present invention, when the gel fraction of the semi-cured product is set to X1 and the gel fraction of the semi-cured product when post-cured under active energy rays is set to X2, the value of (X1 / X2)×100 is 71 or more and 95 or less. The active energy ray-curable adhesive sheet C of the present invention can have excellent impact resistance after post-curing.
[0053] In addition, in this specification, curing of an active energy ray-curable pressure-sensitive adhesive sheet by active energy rays may also be simply referred to as "post-curing".
[0054] Hereinafter, the active energy ray-curable adhesive sheet A, active energy ray-curable adhesive sheet B, and active energy ray-curable adhesive sheet C of the present invention are referred to as “adhesive sheet A,” “adhesive sheet B,” and “adhesive sheet C,” respectively.
[0055] <(Meth)acrylic polymer>
[0056] First, the (meth) acrylic polymer contained in the adhesive sheet A, the adhesive sheet B and the adhesive sheet C is described. The type of the (meth) acrylic polymer is not particularly limited, and for example, it can be the same as the (meth) acrylic polymer used to form a known adhesive sheet. The (meth) acrylic polymer is particularly preferably a polymer that undergoes a crosslinking reaction by a crosslinking agent described later, that is, the (meth) acrylic polymer is preferably a polymer having a crosslinking functional group. As the crosslinking functional group, for example, a carboxyl group, a hydroxyl group, a glycidyl group, an amino group, etc. can be cited.
[0057] As one embodiment of the (meth)acrylic polymer, there can be mentioned a polymer comprising a (meth)acrylic acid ester unit (a) and a monomer unit (b) having a carboxyl group and / or a hydroxyl group. "(Meth)acrylic acid" means "acrylic acid" or "methacrylic acid", "(meth)acrylate" means "acrylate" or "methacrylate", and "(meth)allyl" means "allyl" or "methallyl".
[0058] In addition, the "unit" in the (meth)acrylic acid ester unit (a) and the monomer unit (b) having a carboxyl group and / or a hydroxyl group means a repeating unit constituting a polymer.
[0059] (Meth)acrylate (a) is a repeating unit derived from a (meth)acrylate compound. Examples of (meth)acrylate compounds include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, n-nonyl (meth)acrylate, isononyl (meth)acrylate, n-decyl (meth)acrylate, isodecyl (meth)acrylate, and the like. Among them, as a (meth)acrylate compound, a (meth)acrylate compound having a linear or branched alkyl group having 4 to 10 carbon atoms, preferably 4 to 8 carbon atoms, is preferably free of hydroxyl and carboxyl groups.
[0060] The (meth)acrylic acid ester unit (a) contained in the (meth)acrylic-based polymer may be one type or two or more types.
[0061] The monomer unit (b) having a carboxyl group is a repeating unit derived from a monomer having a carboxyl group. Examples of the monomer having a carboxyl group include a wide range of known carboxyl group-containing polymerizable monomers, and specific examples thereof include acrylic acid and methacrylic acid.
[0062] The monomer unit (b) having a hydroxyl group is a repeating unit derived from a monomer having a hydroxyl group. Examples of the monomer having a hydroxyl group include a wide range of known hydroxyl-containing polymerizable monomers, and specifically, include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 3-chloro-2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, polyalkylene glycol mono(meth)acrylate, and the like.
[0063] The (meth)acrylic polymer may contain both a monomer unit having a carboxyl group and a monomer unit having a hydroxyl group as monomer units (b), or may contain only one of them as monomer units (b). When the monomer unit (b) contains both a monomer unit having a carboxyl group and a monomer unit having a hydroxyl group, their content ratio is not particularly limited, and the desired adhesive sheet can be obtained at any content ratio.
[0064] In the (meth)acrylic polymer, the content ratio of the (meth)acrylic ester unit (a) and the monomer unit (b) is not particularly limited. For example, in the (meth)acrylic polymer, relative to the total mass of the (meth)acrylic ester unit (a) and the monomer unit (b), 50% by mass or more, preferably 60% by mass or more, more preferably 70% by mass or more, further preferably 80% by mass or more, and particularly preferably 90% by mass or more of the (meth)acrylic ester unit (a) may be contained. In addition, relative to the total mass of the (meth)acrylic ester unit (a) and the monomer unit (b), the content ratio of the (meth)acrylic ester unit (a) is preferably 99% by mass or less, more preferably 98% by mass or less, and further preferably 98% by mass or less.
[0065] In addition, in the present invention, the content of each structural unit in the (meth)acrylic polymer can be regarded as being consistent with the amount of the polymerizable monomer derived from the structural unit used when producing the (meth)acrylic polymer.
[0066] The (meth)acrylic polymer may contain other structural units other than the (meth)acrylate unit (a) and the monomer unit (b) as long as the effect of the present invention is not impaired. For example, other structural units can be widely cited, such as structural units derived from compounds that can be copolymerized with the aforementioned (meth)acrylate compound. As the above-mentioned compounds, specifically, (meth)acrylonitrile, vinyl acetate, styrene, vinyl chloride, vinyl pyrrolidone, vinyl pyridine, etc. can be cited. In addition, amino-containing (meth)acrylates, glycidyl-containing (meth)acrylates, alkoxyalkyl-containing (meth)acrylates, etc. can also be cited.
[0067] The content ratio of the (meth)acrylic acid ester unit (a) and the monomer unit (b) relative to the total mass of all structural units of the (meth)acrylic acid polymer is preferably 90 mass% or more, more preferably 95 mass% or more, and further preferably 99 mass% or more. The (meth)acrylic acid polymer may be composed only of the (meth)acrylic acid ester unit (a) and the monomer unit (b).
[0068] In the (meth)acrylic polymer, the arrangement order of each structural unit is not particularly limited, and for example, a random copolymer, a block copolymer, a graft copolymer, etc. may be formed. However, a random copolymer is preferred in terms of ease of production.
[0069] The weight average molecular weight of the (meth) acrylic polymer is not particularly limited. For example, in terms of easily improving the initial adhesive force of the adhesive sheet, the weight average molecular weight of the (meth) acrylic polymer is preferably 100,000 to 2,000,000, and more preferably 200,000 to 1,500,000. It should be noted that the weight average molecular weight of the (meth) acrylic polymer refers to the value before crosslinking with the crosslinking agent described later. The weight average molecular weight of the (meth) acrylic polymer is a value determined by gel permeation chromatography (GPC) under the following conditions and calculated based on a polystyrene standard.
[0070] Solvent: Tetrahydrofuran
[0071] Column: Shodex KF801, KF803L, KF800L, KF800D (connect 4 columns, made by Showa Denko K.K.)
[0072] Column temperature: 40°C
[0073] Sample concentration: 0.5 mass%
[0074] Detector: RI-2031plus (manufactured by JASCO)
[0075] Pump: RI-2080plus (manufactured by JASCO)
[0076] Flow rate: 0.8 ml / min
[0077] Injection volume: 10μl
[0078] In the GPC measurement, 10 samples of Shodex standard polystyrene (manufactured by Showa Denko K.K.) with Mw=1,320 to 2,500,000 were used as the calibration curve.
[0079] The (meth)acrylic polymer contained in the pressure-sensitive adhesive composition may be one kind or two or more kinds.
[0080] The method for producing the (meth)acrylic polymer is not particularly limited, and the (meth)acrylic polymer can be obtained by, for example, a production method utilizing a known polymerization method. The (meth)acrylic polymer can also be obtained from commercially available products.
[0081] <Diene copolymer having (meth)acrylate moieties at both ends>
[0082] Next, the diene copolymer having a (meth)acrylate moiety at both ends contained in adhesive sheet A, adhesive sheet B, and adhesive sheet C (hereinafter referred to as "diene copolymer") is described. A diene copolymer is a polymer having a diene-based polymer skeleton (main chain polymer) and having a (meth)acrylate moiety at both ends. The (meth)acrylate moiety is, for example, a monovalent group represented by "CH2=C(CH3)COO-". It should be noted that, although it is only marked for the sake of precaution, a diene copolymer is a polymer other than a (meth)acrylic polymer.
[0083] By including a diene copolymer, for adhesive sheet A, the initial adhesive force becomes high, and then, the height difference tracking property is also easily improved. In addition, the diene copolymer easily brings a low relative dielectric constant to the adhesive sheet. By including a diene copolymer, for adhesive sheet B, the water vapor permeability before active energy ray irradiation (before post-curing) becomes low, and then, the height difference tracking property is also easily improved. In addition, the diene copolymer easily brings a low relative dielectric constant to the adhesive sheet. By including a diene copolymer, for adhesive sheet C, the impact resistance after active energy ray irradiation (post-curing state) is improved, and the height difference tracking property is also easily improved. In addition, the diene copolymer easily brings a low relative dielectric constant to the adhesive sheet. And then, adhesive sheet C is also easily improved in terms of the adhesive force to the polarizing plate by including a diene copolymer.
[0084] The aforementioned diene copolymer is preferably a polymer having a 1,2 vinyl structure, or a polymer having a structure in which the 1,2 vinyl structure is hydrogenated. In this case, the initial adhesive force of the adhesive sheet is further improved, and further, the height difference tracking property is also particularly easy to improve. The 1,2 vinyl structure is, for example, a monovalent group represented by CH2=CH-, and the structure in which the 1,2 vinyl structure is hydrogenated is, for example, a monovalent group represented by CH3-CH2-. In the case where the aforementioned diene copolymer is a polymer having a 1,2 vinyl structure, or a polymer having a structure in which the 1,2 vinyl structure is hydrogenated, for example, these structures may be present in the side chains of the diene copolymer.
[0085] The diene copolymer preferably has a polymer skeleton of a polybutadiene skeleton and has the (meth)acrylate moieties at both ends. Thus, for the adhesive sheet A, the initial adhesive force can be particularly improved, the height difference followability can also be particularly improved, and the relative dielectric constant of the adhesive sheet can be further reduced.
[0086] The aforementioned (meth)acrylate moieties at both ends may be directly bonded to the diene polymer as the main chain polymer, or may be indirectly bonded via other moieties. When the aforementioned (meth)acrylate moieties are indirectly bonded via other moieties, for example, they may be bonded to the diene polymer via a urethane bond. The aforementioned (meth)acrylate moieties at both ends may be the same as each other, or may be different from each other.
[0087] The weight average molecular weight of the diene copolymer is not particularly limited, and can be set to 1000 to 5000, for example. As a result, the initial adhesive force of the adhesive sheet A is easily improved, and the height difference followability is also easily improved, and the water vapor permeability of the adhesive sheet B before post-curing is easily reduced, and the height difference followability is also easily improved. The weight average molecular weight of the diene copolymer is a value determined by gel permeation chromatography (GPC) under the following conditions and calculated based on polystyrene, and is the same condition as the weight average molecular weight of the (meth) acrylic polymer.
[0088] The glass transition temperature of the diene copolymer is not particularly limited, but is preferably 0° C. or less, for example. As a result, the initial adhesive force of the adhesive sheet A is easily increased, and the step-adjustability is also easily improved, and the water vapor permeability of the adhesive sheet B before post-curing is easily further reduced, and the step-adjustability is also easily improved. The glass transition temperature of the diene copolymer can be measured using a differential scanning calorimeter (DSC).
[0089] The viscosity of the diene copolymer is preferably, for example, 1000 to 500000 mPa·s / 45°C. In this case, the initial adhesive force of the adhesive sheet A is easily improved, the height difference followability is also particularly easy to improve, and the relative dielectric constant of the adhesive sheet can be further reduced. The viscosity here refers to the value measured by a B-type viscometer (RB-80L manufactured by TOKI).
[0090] The diene copolymer contained in the pressure-sensitive adhesive composition may be contained in the form of only one type, or in the form of two or more types.
[0091] The method for producing the diene copolymer is not particularly limited, and the diene copolymer can be obtained, for example, by a production method utilizing a known polymerization method. The diene copolymer can also be obtained from commercial products, such as TE series manufactured by Nippon Soda Co., Ltd.
[0092] In the adhesive composition, the content of the aforementioned diene copolymer is not particularly limited. For example, the aforementioned adhesive composition preferably contains 0.5 to 30 parts by mass of the aforementioned diene copolymer relative to 100 parts by mass of the aforementioned (meth) acrylic polymer. In this case, in adhesive sheet A, the initial adhesion is easy to improve, the height difference tracking property is also easy to improve, and the relative dielectric constant of the adhesive sheet can be further reduced. In adhesive sheet B, the water vapor permeability before post-curing is easy to become lower, the height difference tracking property is also easy to improve, and the relative dielectric constant of the adhesive sheet can be further reduced. In adhesive sheet C, the impact resistance after irradiation with active energy rays is particularly easy to improve, and the height difference tracking property is also particularly easy to improve. In addition, the relative dielectric constant of the adhesive sheet can also be further reduced, and the adhesion to the polarizing plate is also easy to improve.
[0093] The pressure-sensitive adhesive composition more preferably contains 1 part by mass or more of the diene copolymer relative to 100 parts by mass of the (meth)acrylic polymer, further preferably 2 parts by mass or more, particularly preferably 4 parts by mass or more, and more preferably 20 parts by mass or less, further preferably 18 parts by mass or less, particularly preferably 16 parts by mass or less.
[0094] <Photopolymerization initiator>
[0095] Next, the photopolymerization initiator contained in the adhesive sheet A, the adhesive sheet B and the adhesive sheet C is described. The photopolymerization initiator is a component that plays a role in initiating the polymerization reaction of the aforementioned diene copolymer by irradiation with active energy rays (i.e., post-curing). In the present invention, "active energy rays" refer to those having energy quanta in electromagnetic waves or charged particle beams, and ultraviolet rays, electron beams, visible rays, X-rays, ion beams, etc. can be cited. Among them, ultraviolet rays or electron beams are preferred, and ultraviolet rays are particularly preferred from the perspective of versatility.
[0096] The type of photopolymerization initiator is not particularly limited, and examples thereof include a wide range of known photopolymerization initiators. Examples of the photopolymerization initiator include acetophenone-based initiators, benzoin ether-based initiators, benzophenone-based initiators, hydroxyalkylphenone-based initiators, thioxanthone-based initiators, and amine-based initiators.
[0097] As acetophenone-based initiators, specifically, diethoxyacetophenone, benzil dimethyl ketal, etc. can be cited. As benzoin ether-based initiators, specifically, benzoin, benzoin methyl ether, etc. can be cited. As benzophenone-based initiators, specifically, benzophenone, methyl o-benzoylbenzoate, 2,4,6-trimethylbenzophenone mesitylene (phenyl) ketone, 4-methylbenzophenone, etc. can be cited, and it can also be a mixture of 2,4,6-trimethylbenzophenone mesitylene (phenyl) ketone and 4-methylbenzophenone. As hydroxyalkyl phenone-based initiators, specifically, 1-hydroxy-cyclohexyl-phenyl-ketone, etc. can be cited. As thioxanthone-based initiators, specifically, 2-isopropylthioxanthone, 2,4-dimethylthioxanthone, etc. can be cited. As amine-based initiators, specifically, triethanolamine, ethyl 4-dimethylbenzoate, etc. can be cited.
[0098] The photopolymerization initiator contained in the pressure-sensitive adhesive composition may be a single type or two or more types. The photopolymerization initiator can be obtained from, for example, a commercially available product.
[0099] In the adhesive composition, the content of the photopolymerization initiator is not particularly limited and can be appropriately selected according to the type and content of the diene copolymer, the irradiation amount of active energy rays during semi-curing or post-curing, etc. For example, the adhesive composition may contain 0.05 to 10 parts by mass of the photopolymerization initiator relative to 100 parts by mass of the (meth)acrylic polymer, preferably 0.1 to 5 parts by mass.
[0100] <Adhesive composition>
[0101] Next, the adhesive composition used for producing the adhesive sheet A, the adhesive sheet B, and the adhesive sheet C will be described. The adhesive composition may further contain a crosslinking agent in addition to the (meth)acrylic polymer, the diene copolymer, and the photopolymerization initiator.
[0102] The crosslinking agent is, for example, a compound having a property of reacting with a (meth) acrylic polymer by heat. Examples of the crosslinking agent include isocyanate compounds, epoxy compounds, oxazoline compounds, aziridine compounds, metal chelate compounds, and butylated melamine compounds. In terms of high reactivity with (meth) acrylic polymers, isocyanate compounds and epoxy compounds are preferably used as the crosslinking agent. When the crosslinking agent includes a metal chelate, for example, it is also preferred to use a known crosslinking delay agent in combination.
[0103] Examples of the isocyanate compound include toluene diisocyanate, xylylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, etc. Examples of the epoxy compound include ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, glycerol diglycidyl ether, neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, tetraglycidyl xylene diamine, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, trimethylolpropane polyglycidyl ether, diglycerol polyglycidyl ether, polyglycerol polyglycidyl ether, and sorbitol polyglycidyl ether.
[0104] The crosslinking agent contained in the pressure-sensitive adhesive composition may be a single type or two or more types. The crosslinking agent can be obtained from, for example, a commercially available product.
[0105] In the adhesive composition, the content of the crosslinking agent is not particularly limited, and for example, it can be set to 0.01 to 5 parts by mass per 100 parts by mass of the total mass of the (meth) acrylic polymer. In this case, the processability of the obtained adhesive sheet is easily improved. The content of the crosslinking agent can be set to 0.05 to 3 parts by mass per 100 parts by mass of the total mass of the crosslinkable (meth) acrylic copolymer.
[0106] The adhesive composition may also include a silane coupling agent. The type of silane coupling agent is not particularly limited, and for example, known compounds may be widely used. As a silane coupling agent, for example, γ-acryloxypropyl trimethoxysilane, γ-glycidoxypropyl methyl dimethoxysilane, γ-glycidoxypropyl trimethoxysilane, γ-glycidoxypropyl dialkoxysilane, γ-aminopropyl triethoxysilane, γ-aminopropyl trimethoxysilane, γ-glycidoxypropyl trialkoxysilane, γ-methacryloxypropyl trialkoxysilane, γ-chloropropyl trialkoxysilane, γ-methacryloxypropyl dialkoxysilane, γ-mercaptopropyl trialkoxysilane, vinyl trialkoxysilane, etc. may be cited. In addition, the silane coupling agent may also be an oligomer of various alkoxysiloxanes. These silane coupling agents may all be obtained from commercially available products.
[0107] When the pressure-sensitive adhesive composition contains a silane coupling agent, the content ratio thereof can be 0.1 to 5 parts by mass per 100 parts by mass of the (meth)acrylic polymer. The silane coupling agent may be used alone or in combination of two or more.
[0108] From the viewpoint of making coating properties good, the adhesive composition may contain a solvent. Examples of the solvent include hydrocarbons such as hexane, heptane, octane, toluene, xylene, ethylbenzene, cyclohexane, and methylcyclohexane; halogenated hydrocarbons such as dichloromethane, trichloroethane, trichloroethylene, tetrachloroethylene, and dichloropropane; alcohols such as methanol, ethanol, propanol, isopropyl alcohol, butanol, isobutyl alcohol, and diacetone alcohol; ethers such as ethyl ether, diisopropyl ether, dioxane, and tetrahydrofuran; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, isophorone, and cyclohexanone; esters such as methyl acetate, ethyl acetate, butyl acetate, isobutyl acetate, amyl acetate, and ethyl butyrate; polyols such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monomethyl ether acetate, propylene glycol monomethyl ether, propylene glycol monoethyl ether, and propylene glycol monomethyl ether acetate, and derivatives thereof.
[0109] When the adhesive composition includes a solvent, its content is not particularly limited, for example, it can be set to 25 to 500 parts by mass, more preferably 30 to 400 parts by mass, relative to 100 parts by mass of the (meth) acrylic polymer. In addition, the content of the solvent is preferably 10 to 90% by mass, more preferably 20 to 80% by mass, relative to the total mass of the adhesive composition. The solvent can be used alone or in combination of two or more, and when two or more are used, the total mass is preferably within the above range.
[0110] The adhesive composition may contain various adhesive additives other than the above within the scope that does not impair the effect of the present invention. As the above additives, for example, it can be selected from plasticizers, antioxidants, metal corrosion inhibitors, tackifiers, ultraviolet absorbers, hindered amine compounds and other light stabilizers as needed. In addition, dyes and pigments can be added for the purpose of coloring.
[0111] As other components contained in the adhesive composition, polymerizable monomers can be cited. As polymerizable monomers, multifunctional polymerizable monomers and monofunctional monomers can be cited. Hereinafter, polymerizable monomers are recorded as "polymerizable monomers M". It is just marked for the sake of precaution, but polymerizable monomers M refer to components other than diene copolymers. The type of polymerizable monomer M is not particularly limited, for example, known multifunctional polymerizable monomers and monofunctional monomers for manufacturing adhesive sheets can be widely cited.
[0112] However, in the present invention, the adhesive composition preferably does not contain a specific polymerizable monomer described later, and even if it contains the specific polymerizable monomer, it is preferably used in a small amount. Specifically, the so-called specific polymerizable monomer here can be a monofunctional acrylic monomer with a molecular weight lower than 1000. Even if it is included, its content is preferably less than 5 parts by mass, more preferably less than 1 part by mass, further preferably less than 0.1 parts by mass, and particularly preferably less than 0.05 parts by mass per 100 parts by mass of (meth) acrylic polymer. The adhesive composition particularly preferably does not contain a monofunctional acrylic monomer with a molecular weight lower than 1000. The adhesive composition is not containing a specific polymerizable monomer described later, so that the initial adhesion is easily improved in the adhesive sheet A, the water vapor permeability before post-curing is easily further reduced in the adhesive sheet B, and the impact resistance is easily increased in the adhesive sheet C.
[0113] As other examples of specific polymerizable monomers, monofunctional acrylic monomers having an alkyl group having a linear or branched structure and having 8 to 24 carbon atoms can be cited. Even if such monomers are included, their content is preferably less than 5 parts by mass, more preferably less than 1 part by mass, further preferably less than 0.1 part by mass, and particularly preferably less than 0.05 part by mass per 100 parts by mass of the (meth)acrylic polymer. It is particularly preferred that the adhesive composition does not contain a monofunctional acrylic monomer having an alkyl group having a linear or branched structure and having 8 to 24 carbon atoms.
[0114] The adhesive composition also preferably does not contain both a monofunctional acrylic monomer having a molecular weight of less than 1000 and a monofunctional acrylic monomer having an alkyl group having a linear or branched structure and having a carbon number of 8 to 24. Although it is not intended to be interpreted restrictively, when the adhesive sheet C contains these monofunctional acrylic monomers, the monomers bring about a plasticizing effect. Therefore, when the adhesive sheet is post-cured, if there is a portion that is not irradiated with active energy rays, the plasticizing effect of the monofunctional acrylic monomer acts on this portion. It is inferred that the impact resistance of this portion is reduced, and the impact resistance of the adhesive sheet C as a whole after post-curing is impaired.
[0115] Therefore, when the adhesive composition contains a polymerizable monomer M, it is most preferred that the polymerizable monomer M excludes a monofunctional acrylic monomer having a molecular weight of less than 1000 and a monofunctional acrylic monomer having an alkyl group having a linear or branched structure with a carbon number of 8 to 24. When the polymerizable monomer M is other than a monofunctional acrylic monomer having a molecular weight of less than 1000 and a monofunctional acrylic monomer having an alkyl group having a linear or branched structure with a carbon number of 8 to 24, the content thereof is preferably 0.05 to 10 parts by mass, and more preferably 0.1 to 5 parts by mass per 100 parts by mass of the (meth)acrylic polymer. It is also preferred that the adhesive composition does not contain a polymerizable monomer M.
[0116] The preparation method of the adhesive composition is not particularly limited. For example, the adhesive composition can be prepared by mixing a pre-synthesized (meth)acrylic polymer, a photopolymerization initiator, a diene copolymer having (meth)acrylate moieties at both ends, and other components (such as a cross-linking agent, a silane coupling agent, a solvent, etc.) as required in a prescribed ratio. In this case, the (meth)acrylic polymer can be used in the form of a solution or a dispersion. In the case where the (meth)acrylic polymer is a solution or a dispersion, the solution or dispersion may contain the aforementioned solvent. The solution or dispersion of the (meth)acrylic polymer having a functional group can be, for example, 1 to 50% by mass in terms of solid content concentration.
[0117] <Adhesive Sheet>
[0118] The adhesive sheets A, B and C (hereinafter sometimes referred to as "adhesive sheets A to C") of the present invention include a layered semi-cured product formed from the above-mentioned adhesive composition. The semi-cured product functions as an adhesive layer of the adhesive sheet.
[0119] The semi-cured material at least comprises: a cured material of a (meth)acrylic polymer, the aforementioned photopolymerization initiator, and the aforementioned diene copolymer (a diene copolymer having a (meth)acrylate moiety at both ends). The cured material of a (meth)acrylic polymer is, for example, a cross-linked polymer generated by the reaction of the aforementioned (meth)acrylic polymer with the aforementioned cross-linking agent. However, the semi-cured material sometimes also contains unreacted (meth)acrylic polymer and cross-linking agent. It should be noted that the method for forming the semi-cured material is described in the <Method for producing an adhesive sheet> described later.
[0120] The pressure-sensitive adhesive sheets A to C of the present invention may be formed only of the semi-cured product, or may have a layer other than the semi-cured product. Hereinafter, the semi-cured product may be referred to as a "pressure-sensitive adhesive layer".
[0121] As long as the adhesive sheets A to C have the aforementioned adhesive layer, there is no particular limitation on their structure. The adhesive sheet may be a single-sided adhesive sheet or a double-sided adhesive sheet. When the adhesive sheet is a single-sided adhesive sheet, a multilayer sheet having a semi-cured material (adhesive layer) laminated on a support may be cited. In addition, other layers may be provided between the support and the adhesive layer. When the adhesive sheet is a double-sided adhesive sheet, a single-layer adhesive sheet formed by a semi-cured material (adhesive layer), a multilayer adhesive sheet having a plurality of adhesive layers laminated thereon, a multilayer adhesive sheet having other adhesive layers laminated therebetween, and a multilayer adhesive sheet having a support laminated therebetween. When the double-sided adhesive sheet has a support, a transparent support is preferably used as the support. Since the transparency of this double-sided adhesive sheet as a whole is also excellent, it can be suitable for bonding optical components to each other.
[0122] Examples of the support include plastic films such as polystyrene, styrene-acrylic acid copolymer, acrylic resin, polyethylene terephthalate, polycarbonate, polyetheretherketone, triacetylcellulose, and the like; optical films such as antireflection films and electromagnetic wave shielding films; and the like.
[0123] The adhesive layer may be covered by a release sheet, in which case an adhesive sheet with a release sheet is provided. Therefore, an adhesive sheet with a release sheet can be formed by using the adhesive sheet of the present invention. As the release sheet, a peelable laminate having a release sheet substrate and a release agent layer provided on one side of the release sheet substrate, or a polyolefin film such as a polyethylene film or a polypropylene film as a low-polarity substrate can be cited. Paper and polymer films are used as the release sheet substrate in the peelable laminate.
[0124] As the release agent constituting the release agent layer, for example, a general-purpose addition-type or condensation-type silicone release agent or a long-chain alkyl compound can be used. It is particularly preferred to use an addition-type silicone release agent with high reactivity. As the silicone release agent, specifically, BY24-4527, SD-7220, etc. manufactured by Dow Corning Toray Silicone Co., Ltd., KS-3600, KS-774, X62-2600, etc. manufactured by Shin-Etsu Chemical Co., Ltd. can be cited. In addition, it is preferred to contain a silicone release agent having SiO2 units and (CH3)3SiO 1 / 2 Unit or CH2=CH(CH3)SiO 1 / 2 The organosilicon compound having a unit is an organosilicon resin. Specific examples of the organosilicon resin include BY24-843, SD-7292, SHR-1404 and the like manufactured by Dow Corning Toray Silicone Co., Ltd., and KS-3800 and X92-183 and the like manufactured by Shin-Etsu Chemical Co., Ltd.
[0125] When the adhesive layer has release sheets on both sides, the release sheets may have different releasability. If the release from one side is different from the release from the other side, it is easy to first release only the release sheet with high releasability.
[0126] The thickness of the adhesive layer can be appropriately set according to the application, and therefore, is not particularly limited. For example, the thickness of the adhesive layer is preferably 10 to 1000 μm, more preferably 20 to 500 μm, and further preferably 100 to 400 μm. It should be noted that, when the adhesive layer has a multi-layer laminated structure, the thickness of the adhesive layer refers to the total thickness of each layer.
[0127] (Adhesive Sheet A)
[0128] For adhesive sheet A, when the adhesive strength to glass before curing with active energy rays is X1 and the adhesive strength to glass after curing with active energy rays is X2, X1 is 20 N / 25 mm or more, and the value of X1 / X2 is 0.8 or more. The glass here is soda glass (manufactured by Hiraoka Special Glass Manufacturing Co., Ltd., 1.1 mm thick).
[0129] When X1 is 20 N / 25 mm or more and the value of X1 / X2 is 0.8 or more, the pressure-sensitive adhesive sheet of the present invention has excellent initial adhesive strength.
[0130] Here, in the measurement of X2 "curing with active energy rays", the irradiation conditions of the active energy rays are 120 mW / cm at a wavelength of 355 nm. 2 、The accumulated light intensity is 3000mJ / cm 2 The illuminometer used was "UV-PFA1" manufactured by Eye Graphics Co., Ltd. Under the irradiation conditions, an ultraviolet irradiator was used, ECS-4011GX / N manufactured by Eye Graphics Co., Ltd., on which a high-pressure mercury lamp H04-L41 and a heat-ray cutoff filter were installed. Hereinafter, the irradiation conditions are referred to as "irradiation conditions A".
[0131] X1 is preferably 25 N / 25 mm or more, more preferably 30 N / 25 mm or more. The upper limit of X1 is not particularly limited, for example, 50 N / 25 mm. The value of X1 / X2 is preferably 0.82 or more, more preferably 0.84 or more, and further preferably 0.85 or more. The value of X1 / X2 may be less than 1, or the value of X1 / X2 may be 1 or more.
[0132] The pressure-sensitive adhesive sheet A contains at least a crosslinked structure of a (meth)acrylic polymer, the photopolymerization initiator, and the diene copolymer. In particular, the inclusion of the diene copolymer increases the value of X1 and allows the value of X1 / X2 to be large.
[0133] Therefore, even if there is a part of the adhesive sheet A that is not irradiated with active energy rays during post-curing, the adhesive force of this part is high enough to show an adhesive force close to the adhesive force of the post-cured part, resulting in the adhesive sheet A being able to exhibit excellent adhesive performance.
[0134] In the case where the adhesive sheet A does not contain the aforementioned monofunctional acrylic monomer with a molecular weight lower than 1000 and / or a monofunctional acrylic monomer having an alkyl group with a straight or branched structure and a carbon number of 8 to 24, the value of X1 becomes larger, that is, the initial adhesive force is easily improved. It is not intended to be interpreted restrictively, but in the case where the adhesive sheet A contains these monofunctional acrylic monomers, the monomers will also bring a plasticizing effect. Therefore, even if there is a part of the adhesive sheet A that is not irradiated by active energy rays during the post-curing of the adhesive sheet A, the plasticizing effect of the aforementioned monofunctional acrylic monomer also acts on this part. It is speculated that this will lead to a decrease in the adhesive force of this part.
[0135] The relative dielectric constant at 100 kHz after the adhesive sheet is cured under the irradiation condition A is, for example, 3.5 or less. Since the adhesive sheet A has a low relative dielectric constant, the adhesive sheet A of the present invention is suitable for various applications such as display devices such as liquid crystals and organic EL, and in particular, it becomes easy to prevent malfunctions of touch sensors of mobile terminals.
[0136] The relative dielectric constant of the adhesive sheet A after active energy ray curing can be controlled, for example, by adjusting the type and content of the aforementioned diene copolymer. The relative dielectric constant of the adhesive sheet A after active energy ray curing is a value measured at a frequency of 100 KHz, at 23° C., and at 50% RH, and is calculated by the method specified in JIS C 2138.
[0137] The gel fraction of the adhesive sheet A is not particularly limited. The gel fraction of the adhesive sheet A (before irradiation under the irradiation condition A) is, for example, 35% or more, preferably 40% or more, more preferably 45% or more, particularly preferably 50% or more, and the upper limit is, for example, 70%. In addition, the gel fraction of the adhesive sheet after curing under the irradiation condition A is, for example, 55% or more, preferably 60% or more, more preferably 65% or more, particularly preferably 70% or more, and the upper limit is, for example, 95%.
[0138] The gel fraction is a value measured by the following method. First, collect about 0.1 g of the adhesive sheet in a sample bottle, add 30 ml of ethyl acetate, and shake for 24 hours. Then, filter the contents of the sample bottle with a 150-mesh stainless steel wire mesh, dry the residue on the wire mesh at 100°C for 1 hour, and measure the dry mass (g). The gel fraction is calculated from the obtained dry mass according to the following formula 1.
[0139] Gel fraction (mass %) = (dry mass / collected mass of adhesive sheet) × 100 ... Formula 1
[0140] The existing active energy ray-curable adhesive sheet has the problem of low initial adhesive force, that is, the adhesive force before irradiation with active energy rays. In addition, when a display device equipped with an active energy ray-curable adhesive sheet is irradiated with active energy rays to post-cure the adhesive sheet, if there is a frame of the display, the active energy rays do not irradiate the adhesive sheet in that part, so that post-curing of that part is difficult to perform, resulting in insufficient adhesive force, which may also be a problem. In this regard, the adhesive sheet A has excellent initial adhesive force, so the above problem can be overcome.
[0141] (Adhesive sheet B)
[0142] Regarding the pressure-sensitive adhesive sheet B, when the water vapor permeability before curing with active energy rays is defined as Y1 and the water vapor permeability after curing with active energy rays is defined as Y2, Y1 is 200 g / (m 2 · 24 hr) or less, and the value of Y1 / Y2 is less than 1.5. It should be noted that in this specification, the water vapor permeability of the pressure-sensitive adhesive sheet B refers to the water vapor permeability when the thickness of the pressure-sensitive adhesive sheet is converted to 100 μm.
[0143] Y1 is 200g / (m 2 When the Y1 / Y2 value is less than 1.5, the pressure-sensitive adhesive sheet of the present invention has a low water vapor transmission rate even before post-curing.
[0144] Here, in the “curing with active energy rays” when measuring Y2, the irradiation conditions of the active energy rays are the same as the irradiation conditions A described above.
[0145] Y1 is preferably 195 g / (m 2 ·24hr) or less, more preferably 190g / (m 2 The value of Y1 / Y2 is preferably 1.4 or less, more preferably 1.3 or less, and further preferably 1.2 or less. The lower limit of Y1 / Y2 is, for example, 1.
[0146] The pressure-sensitive adhesive sheet B contains at least a crosslinked structure of a (meth)acrylic polymer, the photopolymerization initiator, and the diene copolymer. In particular, the inclusion of the diene copolymer reduces the value of Y1 and allows the value of Y1 / Y2 to be small.
[0147] Therefore, even if there is a portion of the adhesive sheet that is not irradiated with active energy rays during post-curing of the adhesive sheet B, the water vapor permeability of this portion is sufficiently low and can exhibit a water vapor permeability close to that of the post-cured portion, resulting in the adhesive sheet B having a lower water vapor permeability. Thus, when the adhesive sheet is used in electronic devices such as display devices (e.g., organic EL light-emitting elements), damage to the device caused by water vapor can be suppressed.
[0148] In the case where the adhesive sheet does not contain the aforementioned monofunctional acrylic monomers with a molecular weight lower than 1000 and / or monofunctional acrylic monomers with an alkyl group having a straight or branched structure and a carbon number of 8 to 24, the value of Y1 becomes smaller, that is, the water vapor permeability tends to become lower. It is not intended to be interpreted restrictively, but in the case where the adhesive sheet contains these monofunctional acrylic monomers, the monomers also bring about a plasticizing effect. Therefore, even if there is a part of the adhesive sheet that is not irradiated with active energy rays during post-curing of the adhesive sheet, the plasticizing effect of the aforementioned monofunctional acrylic monomers also acts on this part. It is speculated that this will cause the water vapor permeability of this part to become higher.
[0149] The relative dielectric constant of the adhesive sheet B at 100 kHz after curing under the irradiation condition A is, for example, 3.5 or less. Since the adhesive sheet B has a low relative dielectric constant, the adhesive sheet B of the present invention is suitable for various applications such as display devices such as liquid crystals or organic EL, and in particular, it becomes easy to prevent malfunctions of touch sensors of mobile terminals.
[0150] The relative dielectric constant of the adhesive sheet B after active energy ray curing can be controlled, for example, by adjusting the type and content of the aforementioned diene copolymer. The relative dielectric constant of the adhesive sheet B after active energy ray curing is a value measured at a frequency of 100 KHz, 23° C., and 50% RH, and is calculated by the method specified in JIS C 2138.
[0151] The gel fraction of the adhesive sheet B is not particularly limited. The gel fraction of the adhesive sheet (before irradiation under the irradiation condition A) is, for example, 35% or more, preferably 40% or more, more preferably 45% or more, particularly preferably 50% or more, and the upper limit is, for example, 70%. In addition, the gel fraction of the adhesive sheet B after curing under the irradiation condition A is, for example, 55% or more, preferably 60% or more, more preferably 65% or more, particularly preferably 70% or more, and the upper limit is, for example, 95%.
[0152] The gel fraction can be measured by the same method as the method for measuring the gel fraction of the pressure-sensitive adhesive sheet A.
[0153] Although most existing active energy ray-curable adhesive sheets have a desired water vapor permeability after post-curing, there is a problem that the initial water vapor permeability, that is, the water vapor permeability before irradiation with active energy rays, is high. In addition, when a display device equipped with an active energy ray-curable adhesive sheet is irradiated with active energy rays to post-cure the adhesive sheet, if there is a frame of the display, the active energy rays are not irradiated to the adhesive sheet in this part, so that post-curing of this part is difficult to perform, and as a result, the water vapor permeability of this part becomes insufficient, which may also become a problem. In this regard, the initial water vapor permeability of the adhesive sheet B of the present invention is also low, so the above-mentioned problem can be overcome.
[0154] (Adhesive Sheet C)
[0155] For the adhesive sheet C of the present invention, when the gel fraction of the semi-cured product is defined as Z1 and the gel fraction of the semi-cured product after post-curing under active energy rays is defined as Z2, the value of (Z1 / Z2)×100 is 71 or more and 95 or less. Thus, the adhesive sheet of the present invention can have excellent impact resistance after post-curing, and the change in gel fraction before and after post-curing (complete curing) is small, so that even if a component such as a display is bonded to the active energy ray-curable adhesive sheet of the present invention and then irradiated with active energy rays, the strain of the component can be suppressed.
[0156] Here, in the “post-curing with active energy rays” when measuring Z2, the irradiation conditions of the active energy rays are the same as the irradiation conditions A described above.
[0157] Z1 is preferably 70% or less, more preferably 65% or less. The lower limit of Z1 is not particularly limited, and is, for example, 55%. Z2 is preferably 70% or more, more preferably 75% or more, and further preferably 80% or more. The upper limit of Z2 is not particularly limited, and is, for example, 95%.
[0158] The value of (Z1 / Z2)×100 is not particularly limited as long as it is 71 or more and 95 or less, but is preferably 75 or more, and more preferably 80 or more. (Z1 / Z2)×100 is preferably 93 or less, more preferably 90 or less, and further preferably 88 or less.
[0159] The pressure-sensitive adhesive sheet contains at least a cross-linked structure of a (meth)acrylic polymer, the aforementioned photopolymerization initiator and the aforementioned diene copolymer. In particular, by including a diene copolymer and performing a semi-curing treatment by irradiation with active energy rays as described later, the value of Z1 becomes larger, and the value of (Z1 / Z2)×100 can also show a larger value.
[0160] If there is a part of the adhesive sheet that is not irradiated by active energy rays during post-curing, the hardness in the adhesive sheet will fluctuate, so strain occurs, and it is speculated that this will cause the impact resistance of the adhesive sheet to decrease. In contrast, even if there is a part of the adhesive sheet of the present invention that is not irradiated by active energy rays for post-curing (complete curing), the difference in gel fraction is smaller than that of the part irradiated with active energy rays. Therefore, it is not easy to fluctuate in the hardness in the adhesive sheet, so it is not easy to strain, and the result can show excellent impact resistance.
[0161] The gel fraction is a value measured by the following method. First, collect about 0.1 g of the adhesive sheet before or after post-curing in a sample bottle, add 30 ml of ethyl acetate, and shake for 24 hours. After that, filter the contents of the sample bottle with a 150-mesh stainless steel wire mesh, dry the residue on the wire mesh at 100°C for 1 hour, and measure the dry mass (g). The gel fraction is calculated from the obtained dry mass according to the following formula 2.
[0162] Gel fraction (mass %) = (dry mass / collected mass of adhesive sheet) × 100 ... Formula 2
[0163] In recent years, the fields of display devices and the like have been further promoted to achieve high performance and precision, and therefore, there is also a strong demand for improving the performance of adhesive sheets used for bonding displays, etc., and in particular, for further improving impact resistance. In this regard, the adhesive sheet C has excellent impact resistance after post-curing, and therefore can meet the above requirements.
[0164] (Other characteristics of adhesive sheets A to C)
[0165] The haze of the adhesive sheets A to C of the present invention is not particularly limited. For example, the haze of the adhesive sheets A to C of the present invention after being stored in a dry environment at 85°C for 10 days and in an environment at 60°C and a relative humidity of 95% for 10 days is 1% or less, preferably 0.5% or less.
[0166] In addition, the haze of the adhesive sheets A to C of the present invention after the durability test by ultraviolet exposure is 1% or less, preferably 0.5% or less. The durability test by ultraviolet exposure is performed as follows: at 60°C and 0.63 mW / cm 2 The adhesive sheet was irradiated with an illumination of 1000 nm for 4 hours, and then stored under condensation conditions at 50° C. for 4 hours. This treatment was performed 12 times in total.
[0167] The total light transmittance of the adhesive sheets A to C of the present invention is not particularly limited. For example, the total light transmittance (measured in accordance with JIS K 7361-1:1997) of the adhesive sheets of the present invention after being stored at 85°C for 10 days and at 60°C and 95% relative humidity for 10 days is 85% or more, preferably 90% or more. In addition, the total light transmittance of the adhesive sheets A to C of the present invention after the aforementioned durability test based on ultraviolet exposure is 85% or more, preferably 90% or more.
[0168] The b* value of the adhesive sheets A to C of the present invention is not particularly limited. For example, the b* values of the adhesive sheets A to C of the present invention after being stored at 85°C for 10 days and at 60°C and 95% relative humidity for 10 days are all 1 or less, preferably 0.5 or less. In addition, the b* values of the adhesive sheets of the present invention after the aforementioned durability test based on ultraviolet exposure are all 1 or less, preferably 0.5 or less.
[0169] The pressure-sensitive adhesive sheets A to C of the present invention have the above-mentioned optical properties (haze, total light transmittance, b* value) and can satisfy the transparency required when the pressure-sensitive adhesive sheets A to C are used for optical members. They are also excellent in resistance to whitening under humidity and are therefore suitable for optical applications.
[0170] 2. Method for manufacturing adhesive sheet
[0171] The method for producing the adhesive sheets A to C of the present invention (hereinafter referred to as "the adhesive sheets of the present invention") is not particularly limited, and for example, a known method for producing an active energy ray-curable adhesive sheet can be widely used. For example, the adhesive sheet of the present invention can be obtained by a production method comprising the following steps: a step of applying an adhesive composition to form a coating film; and a step of curing the coating film to form a semi-cured product.
[0172] The method for forming the film of the adhesive composition is not particularly limited, for example, a known coating method can be widely used. For example, a commercially available coating device such as a blade coater, an air knife coater, a roll coater, a rod coater, a gravure coater, a micro gravure coater, a bar knife coater, a lip coater, a die coater, a curtain coater can be used to form a film. The coating amount of the adhesive composition is not particularly limited, and can be suitably set according to the thickness of the adhesive layer of the target adhesive sheet. The film can be formed on a suitable substrate, for example, a film can be formed on a release sheet.
[0173] The method for curing the coating to form a semi-cured product is not particularly limited. For example, in the case of adhesive sheet A and adhesive sheet B, it is preferred to form a semi-cured product by heating the coating. The heating conditions are not particularly limited, for example, the coating can be heated under conditions of 50°C or more and 150°C or less, and the heating time can be appropriately set according to the heating temperature and the residual solvent concentration of the target adhesive layer, for example, it can be set to 1 to 30 minutes. The heat treatment can use a known heating device such as a heating furnace and an infrared lamp. After the heat treatment, the semi-cured product can be aged under a specified environment as needed.
[0174] In addition, in the case of adhesive sheet C, a method of forming a semi-cured product by irradiating the coating with active energy rays can be cited. When the coating is irradiated with active energy rays, release sheets can be provided on both sides of the coating. The active energy rays are preferably irradiated in such a manner that the gel fraction of the semi-cured product becomes 70% or less. As an example of the irradiation conditions of active energy rays for forming a semi-cured product, "irradiation condition B" can be cited. Irradiation condition B is an illuminance of 120 mW / cm at a wavelength of 355 nm. 2 , the accumulated light intensity is 200~800mJ / cm 2 The illuminometer used was "UV-PFA1" manufactured by Eye Graphics Co., Ltd. Under the irradiation conditions, an ultraviolet irradiation machine was ECS-4011GX / N manufactured by Eye Graphics Co., Ltd., to which a high-pressure mercury lamp H04-L41 and a heat ray cut filter were attached.
[0175] The semi-cured product formed by each of the above methods becomes the adhesive layer of the adhesive sheet. When the adhesive composition contains volatile components such as solvents, they evaporate in the process of forming the semi-cured product. As described above, the semi-cured product at least includes a cross-linked polymer generated by the reaction of the aforementioned (meth) acrylic polymer and the aforementioned cross-linking agent, the aforementioned photopolymerization initiator and the aforementioned diene copolymer (a diene copolymer having a (meth) acrylate site at both ends). However, the semi-cured product sometimes also contains unreacted (meth) acrylic polymers and cross-linking agents. In addition, in the process of forming the semi-cured product, the aforementioned photopolymerization initiator and the aforementioned diene copolymer are sometimes consumed. In adhesive sheets A and B, the aforementioned photopolymerization initiator and the aforementioned diene copolymer remaining in the semi-cured product are preferably 95% by mass or more, preferably 99% by mass or more, respectively, relative to the aforementioned photopolymerization initiator and the aforementioned diene copolymer contained in the adhesive composition.
[0176] As described above, a semi-cured product (adhesive layer) can be formed to obtain the adhesive sheet of the present invention. If necessary, the semi-cured product (adhesive layer) can also be protected on one or both sides with a release sheet, for example, the above-mentioned adhesive sheet with a release sheet is provided.
[0177] (How to use the adhesive sheet)
[0178] The adhesive sheet of the present invention contains the aforementioned photopolymerization initiator and the aforementioned diene copolymer in a semi-cured product, and therefore has active energy ray curing properties. Therefore, the adhesive layer of the adhesive sheet is brought into contact with the surface of an adherend, and in this state, active energy rays are irradiated to post-cure the adhesive layer, and in particular, to completely cure it, thereby making it more firmly bonded to the adherend.
[0179] There is no particular restriction on the active energy ray used when post-curing. From the perspective of versatility, ultraviolet rays or electron beams are preferred, and ultraviolet rays are particularly preferred. As the light source of ultraviolet rays, for example, high-pressure mercury lamps, low-pressure mercury lamps, ultrahigh-pressure mercury lamps, metal halide lamps, carbon arc lamps, xenon arc lamps, electrodeless ultraviolet lamps, etc. can be used. As electron beams, for example, electron beams released from various electron beam accelerators such as Cockloft Walt type, Bandecliff type, resonance transformer type, insulating core transformer type, linear type, high-frequency high-voltage accelerator type, and high-frequency type can be used.
[0180] The irradiation conditions of the active energy rays are not particularly limited and can be appropriately set according to the wavelength. For example, the irradiation power of ultraviolet rays is preferably such that the accumulated light amount becomes 100 mJ / cm 2 Above and 10000mJ / cm 2 Below, more preferably 500mJ / cm 2 Above and 5000mJ / cm 2 the following.
[0181] Since the adhesive layer of the adhesive sheet is in a semi-cured state, the adhesive layer can follow the unevenness even if the adherend has a height difference before irradiation with active energy rays. In this way, after the adhesive sheet is attached and made to follow the unevenness, the adhesive layer is completely cured by active energy rays, thereby improving the cohesive force of the adhesive layer and improving durability.
[0182] By using the pressure-sensitive adhesive sheet as described above, a laminated body in which an adherend and the post-cured pressure-sensitive adhesive sheet are laminated can be obtained. Therefore, the laminated body includes the post-cured product of the active energy ray-curable pressure-sensitive adhesive sheet as the pressure-sensitive adhesive layer.
[0183] The type of adherend of the laminate is not particularly limited, and various optical components can be cited, for example. As the optical component, various components in optical products such as touch panels and image display devices can be cited, and specifically, components for liquid crystal or organic EL displays can be exemplified. Components for liquid crystal or organic EL displays can specifically include glass, polarizing plates, or touch sensors.
[0184] Since the initial adhesive force before the active energy ray irradiation is high, even if there is a part that is not irradiated with the active energy ray, it has excellent adhesive force and can be adjusted to a low dielectric constant, the adhesive sheet of the present invention is preferably used for bonding components for liquid crystal or organic EL displays. Therefore, as the aforementioned laminate, it is suitable for display devices, etc.
[0185] The pressure-sensitive adhesive sheet of the present invention can be used for various applications requiring a pressure-sensitive adhesive sheet in addition to the above-mentioned liquid crystal or organic EL display.
[0186] Example
[0187] Hereinafter, the present invention will be described in more detail based on Examples, but the present invention is not limited to the embodiments of these Examples.
[0188] [Evaluation of Adhesive Sheets A and B]
[0189] (Production Example 1)
[0190] 2-Ethylhexyl methacrylate (2-EHMA), 2-ethylhexyl acrylate (2-EHA), and 2-hydroxyethyl methacrylate (2-HEMA) were mixed in a mass ratio of 70:20:10, and 2,2'-azobis(2,4-dimethylvaleronitrile) as a radical polymerization initiator was dissolved in the solution. The solution was heated to 60°C for random copolymerization to obtain a (meth)acrylic polymer having a weight average molecular weight (Mw) of 450,000 and a glass transition temperature (Tg) of -20°C.
[0191] (Components of Adhesive Composition)
[0192] The components contained in the adhesive composition used in each of the Examples and Comparative Examples are as follows.
[0193] <(Meth)acrylic polymer>
[0194] The (meth)acrylic polymer obtained in Production Example 1 was used as the (meth)acrylic polymer.
[0195] <Diene copolymer>
[0196] As the diene copolymer, any of the following two types are used.
[0197] ·"TEAI-1000" manufactured by Japan Soda Co., Ltd. (Mw1000, Tg-14℃)
[0198] ·"TE-2000" made by Japan Soda Co., Ltd. (Mw2000, Tg-9℃)
[0199] <Cross-linking agent>
[0200] A xylene diisocyanate compound ("D-110N" manufactured by Mitsui Chemicals, Inc.) was used as the crosslinking agent.
[0201] <Silane coupling agent>
[0202] As the silane coupling agent, "X-41-1810" manufactured by Shin-Etsu Chemical was used.
[0203] <Photopolymerization initiator>
[0204] As the photopolymerization initiator, any of the following two types are used.
[0205] Omnirad184 (IGM resin)
[0206] EsacureTZT (IGM resin)
[0207] <Monofunctional acrylic monomer>
[0208] As the monofunctional acrylic monomer, any of the following two types are used.
[0209] ·Isostearyl acrylate (ISTA (abbreviated as ISTA), manufactured by Osaka Organic Chemical Industry Co., Ltd., molecular weight 324)
[0210] Isobornyl acrylate (IBXA (abbreviated as IBXA) manufactured by Osaka Organic Chemical Industry Co., Ltd., molecular weight 208)
[0211] <Multi-monofunctional monomer>
[0212] As the polymonofunctional monomer, trifunctional monomer M321 (trimethylolpropane propylene oxide-modified triacrylate, molecular weight 546) manufactured by Toagosei Co., Ltd. was used.
[0213] (Example 1)
[0214] The adhesive composition was prepared according to the mixing conditions shown in Table 1. Specifically, 100 parts by mass (in terms of polymer components) of the (meth) acrylic polymer obtained in Production Example 1, 1 part by mass of a diene copolymer ("TEAI-1000" manufactured by Nippon Soda Co., Ltd.), 0.2 parts by mass of a crosslinking agent, 0.2 parts by mass of a silane coupling agent, and 0.4 parts by mass of a photopolymerization initiator (Omnirad184) were mixed with ethyl acetate as a solvent (E) so that the solid content concentration became 46% by mass to obtain an adhesive composition.
[0215] The adhesive composition was evenly applied using an applicator to a polyethylene terephthalate film having a thickness of 100 μm and having a release agent layer treated with a silicone release agent (referred to as the first release sheet; Oji F-Tex Co., Ltd.: 100RL-07(2)) so that the coating amount after drying was 200 μm / m 2 . During coating, a coating width YD type manufactured by Yoshimitsu Seiki Co., Ltd. was used, and the coating was heated at 100°C for 3 minutes in an air circulation constant temperature oven. Thus, an adhesive layer was formed on the surface of the first release sheet. A second release sheet (manufactured by OjiF-Tex Co., Ltd.: 50RL-07(L)) with a thickness of 50 μm was adhered to the surface of the adhesive layer to obtain an adhesive sheet with a release sheet having a structure of a first release film / adhesive sheet (adhesive layer) / second release film in which a semi-cured material (adhesive layer) is sandwiched between a pair of release films having a difference in release force. For the adhesive sheet, an aging treatment was performed by standing it for 7 days at 23°C and a relative humidity of 50%. The thickness of the adhesive sheet is 200 μm.
[0216] (Examples 2 to 9, Comparative Examples 1 to 4)
[0217] A PSA sheet with a release sheet was obtained in the same manner as in Example 1 except that the types and amounts of the components of the PSA composition were changed to the formulation shown in Table 1. The thickness of each PSA sheet is shown in Table 1.
[0218] [Evaluation of Pressure-Sensitive Adhesive Sheet C]
[0219] The raw materials of the (meth)acrylic polymer, diene copolymer, crosslinking agent, silane coupling agent, photo, monofunctional acrylic monomer and polymonofunctional monomer used in the evaluation of PSA sheet C are all the same as those used in the evaluation of PSA sheet A.
[0220] (Example 11)
[0221] The adhesive composition was prepared according to the mixing conditions shown in Table 1. Specifically, 100 parts by mass (in terms of polymer components) of the (meth) acrylic polymer obtained in Production Example 1, 1 part by mass of a diene copolymer ("TEAI-1000" manufactured by Nippon Soda Co., Ltd.), 0.2 parts by mass of a crosslinking agent, 0.2 parts by mass of a silane coupling agent, and 0.4 parts by mass of a photopolymerization initiator (Omnirad184) were mixed with ethyl acetate as a solvent (E) so that the solid content concentration became 46% by mass to obtain an adhesive composition.
[0222] The adhesive composition was evenly applied using an applicator to a polyethylene terephthalate film having a thickness of 100 μm and having a release agent layer treated with a silicone release agent (referred to as the first release sheet; Oji F-Tex Co., Ltd.: 100RL-07(2)) so that the coating amount after drying was 200 μm / m 2 . During coating, a coating width YD type manufactured by Yoshimitsu Seiki Co., Ltd. was used, and the coating was heated at 100°C for 3 minutes in an air circulation constant temperature oven. Thus, a coating film of the adhesive composition was formed on the surface of the first release sheet. A second release sheet (manufactured by Oji F-Tex Co., Ltd.: 50RL-07(L)) with a thickness of 50 μm was adhered to the surface of the adhesive layer to obtain an adhesive sheet with a release sheet having a structure of a first release film / adhesive sheet (adhesive layer) / second release film in which a semi-cured material (adhesive layer) was sandwiched between a pair of release films having a difference in release force.
[0223] The adhesive sheet with the release sheet was irradiated with ultraviolet light to form a semi-cured product (adhesive layer). The ultraviolet light irradiation was the same as the irradiation condition B described above, that is, the irradiance was 120 mW / cm at a wavelength of 355 nm. 2 , the accumulated light intensity is 600mJ / cm 2 The illuminometer used was "UV-PFA1" manufactured by Eye Graphics Co., Ltd., and the ultraviolet irradiator used was ECS-4011GX / N manufactured by Eye Graphics Co., Ltd., on which a high-pressure mercury lamp H04-L41 and a heat-ray cutoff filter were installed. The adhesive sheet was subjected to an aging treatment at 23°C and a relative humidity of 50% for 7 days. The thickness of the adhesive sheet was 200 μm.
[0224] (Examples 12 to 17, Comparative Examples 6 to 10)
[0225] A pressure-sensitive adhesive sheet with a release sheet was obtained in the same manner as in Example 11 except that the types and amounts of components of the pressure-sensitive adhesive composition and the cumulative amount of ultraviolet light for semi-curing were changed to the formulations shown in Table 2. The thickness of each pressure-sensitive adhesive sheet is shown in Table 1.
[0226] [Table 1]
[0227]
[0228] [Table 2]
[0229]
[0230] Table 1 shows the manufacturing conditions and evaluation results of the adhesive sheet obtained in each embodiment and comparative example. The initial adhesive force of the adhesive sheet (equivalent to the adhesive sheet A and adhesive sheet B of the present invention) obtained in the embodiment is high, and in addition, the relative dielectric constant is also low, and the transparency is also high, and the height difference tracking property is excellent. In contrast, the adhesive sheet obtained in the comparative example is made by the adhesive composition not containing diene copolymer, and includes monofunctional acrylic monomers and / or multi-monofunctional monomers, therefore, the initial adhesive force is low.
[0231] Table 2 shows the manufacturing conditions and evaluation results of the adhesive sheets obtained in each embodiment and comparative example. The values of (Z1 / Z2)×100 of the adhesive sheets obtained in the embodiments (equivalent to the adhesive sheet C of the present invention) all satisfy 71 or more and 95 or less, and have excellent impact resistance, low relative dielectric constant, high transparency, and excellent height difference tracking. In contrast, in Comparative Example 6, no semi-curing treatment was performed, and the value of (Z1 / Z2)×100 was less than 71, so the impact resistance was poor. In Comparative Example 7, the semi-curing treatment was excessively performed, and the value of (Z1 / Z2)×100 was higher than 95, and X1 was too much, so the impact resistance was poor. In addition, the adhesive sheets obtained in Comparative Examples 8 to 10 are made of an adhesive composition that does not contain a diene copolymer, and contain a monofunctional acrylic monomer and / or a multi-monofunctional monomer, so the impact resistance is poor.
[0232] (Evaluation method)
[0233] The pressure-sensitive adhesive sheets obtained in the respective Examples and Comparative Examples were evaluated as follows.
[0234] <Adhesion to glass (initial adhesion)>
[0235] A PET film ("A4300#100" manufactured by Toyobo Co., Ltd.) was used as a lining material, and the adhesive sheet (before post-curing) was bonded to a glass plate (soda glass manufactured by Hiraoka Special Glass Manufacturing Co., Ltd., 1.1 mm thick) using a 2 kg load roller. After being left at 25° C. for 24 hours, the sheet was peeled at 180 degrees at a tensile speed of 300 mm / min (and 3000 mm / min) using a tensile tester (model: RTC-1210, manufactured by A&D) in accordance with JIS Z 0237, and the peel strength at this time was measured and taken as the initial adhesive force (X1) of the adhesive sheet.
[0236] <Adhesion to glass (after post-curing)>
[0237] A PET film ("A4300#100" manufactured by Toyobo Co., Ltd.) was used as a lining material, and the adhesive sheet (before post-curing) was bonded to a glass plate (soda glass manufactured by Hiraoka Special Glass Manufacturing Co., Ltd., 1.1 mm thick) using a 2 kg load roller, and then the adhesive sheet was irradiated with active energy rays from the lining material side under the same conditions as the aforementioned irradiation condition A for post-curing. After the post-cured adhesive sheet was placed at 25°C for 24 hours, it was peeled 180 degrees at a tensile speed of 300 mm / min (and 3000 mm / min) using a tensile testing machine (model: RTC-1210, manufactured by A&D) in accordance with JIS Z 0237, and the peel strength at this time was measured as the adhesive force (X2) of the adhesive sheet after post-curing. It should be noted that the irradiation condition in irradiation condition A is an irradiance of 120 mW / cm at a wavelength of 355 nm. 2 , the accumulated light intensity is 3000mJ / cm 2 The illuminometer used was "UV-PFA1" manufactured by Eye Graphics Co., Ltd. In the irradiation condition A, an ultraviolet irradiator was ECS-4011GX / N manufactured by Eye Graphics Co., Ltd., to which a high-pressure mercury lamp H04-L41 and a heat ray cut filter were attached.
[0238] <Gel Fraction (Examples 1 to 9); Adhesive Sheets A and B>
[0239] About 0.1 g of the adhesive sheet (before or after post-curing) was collected in a sample bottle, 30 ml of ethyl acetate was added, and the mixture was shaken for 24 hours. After that, the contents of the sample bottle were filtered out with a 150-mesh stainless steel mesh, and the residue on the mesh was dried at 100° C. for 1 hour, and the dry mass (g) was measured. The gel fraction was calculated from the obtained dry mass according to the above formula 1. The adhesive sheet post-curing in the measurement of the gel fraction was performed according to the above irradiation condition A.
[0240] <Gel Fraction (Examples 11 to 17); Adhesive Sheet C>
[0241] About 0.1 g of the adhesive sheet (before or after post-curing) was collected in a sample bottle, 30 ml of ethyl acetate was added, and the mixture was shaken for 24 hours. After that, the contents of the sample bottle were filtered out with a 150-mesh stainless steel mesh, and the residue on the mesh was dried at 100°C for 1 hour, and the dry mass (g) was measured. The gel fraction was calculated from the obtained dry mass according to the above formula 1. The post-curing of the adhesive sheet in the determination of the gel fraction was carried out according to the above irradiation condition A. The gel fraction of the adhesive sheet before post-curing (semi-cured state) was set as Z1 (%), and the gel fraction of the adhesive sheet after post-curing was set as Z2 (%), and the value of (Z1 / Z2)×100 was calculated.
[0242] <Relative dielectric constant>
[0243] The post-cured adhesive sheet was sandwiched between two copper foils and subjected to autoclave treatment (40°C, 0.5 MPa, 30 minutes). Thereafter, the dielectric constant was measured using a dielectric constant measurement system (manufactured by TOYO Corporation, Model 1260) in accordance with JIS C 2138. The relative dielectric constant was calculated using the method specified in JIS C 2138 at a frequency of 100 kHz, in an environment of 23°C and 50% RH.
[0244] Durability
[0245] A polyester film (A4360 manufactured by Toyobo Co., Ltd.) having a thickness of 100 μm was laminated to the surface exposed by peeling off the first release film of the adhesive sheet, and then cut into a size of 50 mm×50 mm to obtain a laminate 1. On the other hand, starch particles (NIKKALYCO L manufactured by NIKKA LIMITED) having an average particle size of 20 μm were scattered on a polarizing plate of a glass plate (S3112 manufactured by Matsunami Glass Co., Ltd.) to which a polarizing plate (SKN-18243T-HC manufactured by Polatechno Co., Ltd.) was previously attached to the entire surface, to prepare a laminate 2. The surface of the laminate 2 on which the starch particles were scattered was laminated to the surface exposed by peeling off the second release film of the laminate 1, and then subjected to autoclave treatment (40° C., 0.5 MPa, 30 minutes) to obtain a sample for evaluation. After the sample was stored at 85° C. in a dry environment for 24 hours, the presence or absence of foaming in the sample was evaluated, and the durability was determined based on the following criteria.
[0246] ○: No bubbles, therefore excellent durability.
[0247] ×: There are bubbles, and therefore, the durability is poor.
[0248] <Water vapor transmission rate (before post-curing)>
[0249] The water vapor permeability of the adhesive sheet before post-curing is calculated based on JIS Z0208-1976 and the cup method. An 80 μm adhesive film (TD80ULM (made by Fujifilm) is used as a substrate, and the surface exposed by peeling off the light peeling film of the adhesive sheet is bonded to the aforementioned substrate. Then, the heavy peeling film of the adhesive sheet is peeled off to make a laminate, and the water vapor permeability (Y1) is measured using the laminate. When the laminate is installed in a cup, the outside of the cup becomes the adhesive film and the inside becomes the adhesive layer of the adhesive sheet. The measurement is carried out in the presence of 5 g of calcium chloride, at 40°C and 90% RH. The aforementioned laminate is stored in this environment for 24 hours, and the water vapor permeability per 100 μm of the adhesive sheet is calculated from the mass change of the laminate before and after storage.
[0250] <Water vapor transmission rate (after post-curing)>
[0251] The water vapor permeability of the adhesive sheet after post-curing is calculated based on JIS Z0208-1976 and the cup method. A pair of release sheets of the adhesive sheet with a release sheet are peeled off, and the adhesive sheet is irradiated with active energy rays under the same conditions as the above-mentioned irradiation condition A to post-cure the adhesive sheet. An 80μm adhesive film (TD80ULM (made by Fujifilm) as a substrate is attached to one side of the post-cured adhesive sheet to produce a laminate, and the water vapor permeability (Y2) is measured. When the laminate is installed in a cup, the outside of the cup becomes the adhesive film and the inside becomes the adhesive layer of the adhesive sheet. The measurement environment is set to 40°C and 90% RH. Under this environment, the laminate is stored for 24 hours in the presence of 5g of calcium chloride, and the water vapor permeability per 100μm of the adhesive sheet is calculated from the mass change of the laminate before and after storage. It should be noted that the irradiation condition in irradiation condition A is an illuminance of 120mW / cm at a wavelength of 355nm. 2 , the accumulated light intensity is 3000mJ / cm 2 The illuminometer used was "UV-PFA1" manufactured by Eye Graphics Co., Ltd. In the irradiation condition A, an ultraviolet irradiator was ECS-4011GX / N manufactured by Eye Graphics Co., Ltd., to which a high-pressure mercury lamp H04-L41 and a heat ray cut filter were attached.
[0252] <Adhesion to polarizing plate (low speed)>
[0253] The adhesive strength was measured by the same method as described in the above <Adhesion Strength to Glass (After Post-Curing)> except that the glass plate was changed to a polarizing plate (a glass plate of "AWN-3244EVAG25K" manufactured by Samsung was bonded).
[0254] <Adhesion to polarizing plate (high speed)>
[0255] The adhesive strength was measured in the same manner as in the above-mentioned <Adhesion Strength to Polarizing Plate (Slow Speed)> except that the stretching speed was changed to 3000 mm / min.
[0256] <Impact resistance>
[0257] Prepare a 50mm×90mm×20μm soda glass (height difference glass) with a black window frame print and an adhesive sheet with a release sheet (before post-curing) cut into a size overlapping the black window frame print by 2mm in width. After peeling off the first release sheet of the adhesive sheet with a release sheet, the adhesive sheet roll is bonded to the soda glass, and then the second release sheet is peeled off, and the aforementioned soda glass of the same kind is vacuum bonded to the exposed adhesive surface to obtain a laminate. Then, according to the aforementioned irradiation condition A, the laminate is irradiated with ultraviolet rays from the height difference glass side, and after post-curing, an anti-scattering film ("ME-PET50" manufactured by Shin TAC Chemical Co., Ltd.) is bonded to both sides of the laminate to obtain a measurement sample. The measurement sample is freely dropped from a height of 0.6m in the order of the front side (surface), the back side (back side), the two long sides, and the two short sides, and the presence or absence of peeling is confirmed, and the following criteria are used for evaluation.
[0258] ○: No peeling or bubbles were observed
[0259] ×: Peeling or bubbles were observed.
Claims
1. An active energy ray-curable adhesive sheet comprising: a semi-cured product of an adhesive composition comprising at least a (meth)acrylic polymer, a photopolymerization initiator, and a diene copolymer having (meth)acrylate moieties at both ends; in, The weight average molecular weight of the diene copolymer is 1000 to 5000, In the adhesive composition, the content of the monofunctional acrylic monomer having a molecular weight of less than 1000 is less than 5 parts by mass per 100 parts by mass of the (meth)acrylic polymer. The pressure-sensitive adhesive composition comprises 0.5 to 30 parts by mass of the diene copolymer relative to 100 parts by mass of the (meth)acrylic polymer, When the adhesive force to glass before curing with active energy rays is X1 and the adhesive force to glass after curing with active energy rays is X2, X1 is 20 N / 25 mm or more and the value of X1 / X2 is 0.8 or more.
2. An active energy ray-curable adhesive sheet comprising: a semi-cured product of an adhesive composition comprising at least a (meth)acrylic polymer, a photopolymerization initiator, and a diene copolymer having (meth)acrylate moieties at both ends; in, The weight average molecular weight of the diene copolymer is 1000 to 5000, In the adhesive composition, the content of the monofunctional acrylic monomer having a molecular weight of less than 1000 is less than 5 parts by mass per 100 parts by mass of the (meth)acrylic polymer. The pressure-sensitive adhesive composition comprises 0.5 to 30 parts by mass of the diene copolymer relative to 100 parts by mass of the (meth)acrylic polymer, When the water vapor permeability before curing with active energy rays is defined as Y1 and the water vapor permeability after curing with active energy rays is defined as Y2, Y1 is 200 g / (m 2 24hr) or less, The value of Y1 / Y2 is less than 1.
5.
3. An active energy ray-curable adhesive sheet comprising: a semi-cured product of an adhesive composition comprising at least a (meth)acrylic polymer, a photopolymerization initiator, and a diene copolymer having (meth)acrylate moieties at both ends; in, The weight average molecular weight of the diene copolymer is 1000 to 5000, In the adhesive composition, the content of the monofunctional acrylic monomer having a molecular weight of less than 1000 is less than 5 parts by mass per 100 parts by mass of the (meth)acrylic polymer. The pressure-sensitive adhesive composition comprises 0.5 to 30 parts by mass of the diene copolymer relative to 100 parts by mass of the (meth)acrylic polymer, When the gel fraction of the semi-cured product is Z1 and the gel fraction of the semi-cured product after post-curing under active energy rays is Z2, the value of (Z1 / Z2)×100 is 75 to 88, and Z2 is 70% to 95%.
4. The active energy ray-curable pressure-sensitive adhesive sheet according to any one of claims 1 to 3, wherein In the adhesive composition, the content of the monofunctional acrylic monomer is less than 5 parts by mass per 100 parts by mass of the (meth)acrylic polymer, and the monofunctional acrylic monomer has an alkyl group with 8 to 24 carbon atoms, and the alkyl group has a linear or branched structure.
5. The active energy ray-curable pressure-sensitive adhesive sheet according to any one of claims 1 to 3, wherein The diene copolymer is a polymer having a 1,2 vinyl structure or a polymer having a structure in which a 1,2 vinyl structure is hydrogenated.
6. The active energy ray-curable pressure-sensitive adhesive sheet according to any one of claims 1 to 3, wherein The glass transition temperature of the diene copolymer is 0° C. or lower. 7 . The active energy ray-curable pressure-sensitive adhesive sheet according to claim 1 , wherein the active energy ray-curable pressure-sensitive adhesive sheet has a relative dielectric constant of 3.5 or less at 100 kHz after active energy ray curing.
8. The active energy ray-curable pressure-sensitive adhesive sheet according to any one of claims 1 to 3, which is used for bonding members for liquid crystal or organic EL displays. The component is glass, a polarizing plate, or a touch sensor. 9 . A display device comprising a post-cured product of the active energy ray-curable pressure-sensitive adhesive sheet according to claim 1 as a pressure-sensitive adhesive layer.
Citation Information
Patent Citations
Pressure-sensitive adhesive sheet, process for producing laminate including pressure-sensitive adhesive layer, laminate including pressure-sensitive adhesive layer, image display device, and touch panel
WO2017022770A1
Double-sided adhesive sheet and image display apparatus
CN105452410A
Acrylic adhesive composition and method of producing adhesive tape using the same
JP2014181258A
Pressure sensitive adhesive layer for building material
JP2017132893A